Wright on McKinsey one more time - Dierig, Simon (Logos & Episteme, 2021)
In this essay, Crispin Wright’s various attempts at solving the so-called McKinsey paradox are reconstructed and criticized. In the first section, I argue against Anthony Brueckner that Wright’s solution does require that there is a failure of warrant transmission in McKinsey’s argument. To this end, a variant of the McKinsey paradox for earned a priori warrant is reconstructed, and it is claimed that Wright’s putative solution of this paradox is best understood as drawing on the contention that there is a transmission failure in the argument in question. In section II, I focus on Wright’s views in the second part of his pivotal article on the McKinsey paradox (published in 2003). It is argued that the solution to the paradox proposed there by Wright is convincing if his theory of entitlements is accepted. In the third section, however, I raise an objection against Wright’s account of entitlements. Finally, in section IV, Wright’s views in his most recent essay on the McKinsey paradox are examined. It is shown that his new solution to this problem does not work any better than his earlier attempts at solving it.
Gesehen am 07.04.2021